MR multitasking‐based dynamic imaging for cerebrovascular evaluation (MT‐DICE): Simultaneous quantification of permeability and leakage‐insensitive perfusion by dynamic T1/T2* mapping. Issue 1 (21st September 2022) - Hu, Zhehao; Christodoulou, Anthony G.; Wang, Nan; Xie, Yibin; Shiroishi, Mark S.; Yang, Wensha; Zada, Gabriel; Chow, Frances E.; Margol, Ashley S.; Tamrazi, Benita; Chang, Eric L.; Li, Debiao; et al.
Abstract : Purpose: To develop an MR multitasking‐based dynamic imaging for cerebrovascular evaluation (MT‐DICE) technique for simultaneous quantification of permeability and leakage‐insensitive perfusion with a single‐dose contrast injection. Methods: MT‐DICE builds on a saturation‐recovery prepared multi‐echo fast low‐angle shot sequence. The k‐space is randomly sampled for 7.6 min, with single‐dose contrast agent injected 1.5 min into the scan. MR multitasking is used to model the data into six dimensions, including three spatial dimensions for whole‐brain coverage, a saturation‐recovery time dimension, and a TE dimension for dynamic T 1 $$ T_1 $$ and T 2 * $$ T_2^{* } $$ quantification, respectively, and a contrast dynamics dimension for capturing contrast kinetics. The derived pixel‐wise T 1 / T 2 * $$ T_1/T_2^{* } $$ time series are converted into contrast concentration‐time curves for calculation of kinetic metrics. The technique was assessed for its agreement with reference methods in T 1 $$ T_1 $$ and T 2 * $$ T_2^{* } $$ measurements in eight healthy subjects and, in three of them, inter‐session repeatability of permeability and leakage‐insensitive perfusion parameters. Its feasibility was also demonstrated in four patients with brain tumors. Results: MT‐DICE T 1 / T 2 * $$ T_1/T_2^{* } $$ values of normal gray matter and white matter were in excellent agreement with reference values (intraclass correlation coefficients = 0.860/0.962 for gray matter and 0.925/0.975 for white matter ). Both permeability and perfusion parameters demonstrated good to excellent intersession agreement with the lowest intraclass correlation coefficients at 0.694. Contrast kinetic parameters in all healthy subjects and patients were within the literature range. Conclusion: Based on dynamic T 1 / T 2 * $$ T_1/T_2^{* } $$ mapping, MT‐DICE allows for simultaneous quantification of permeability and leakage‐insensitive perfusion metrics with a single‐dose contrast injection. Abstract : Click here for author‐reader discussions